Use of yeast nuclear DNA sequences to define the mitochondrial RNA polymerase promoter in vitro. - Marczynski, G T (1989)
We have extended an earlier observation that the TATA box for the nuclear GAL10 gene serves as a promoter for the mitochondrial RNA polymerase in in vitro transcription reactions (C. S. Winkley, M. J. Keller, and J. A. Jaehning, J. Biol. Chem. 260:14214-14223, 1985). In this work, we demonstrate that other nuclear genes also have upstream sequences that function in vitro as mitochondrial RNA polymerase promoters. These genes include the GAL7 and MEL1 genes, which are regulated in concert with the GAL10 gene, the sigma repetitive element, and the 2 microns plasmid origin of replication. We used in vitro transcription reactions to test a large number of nuclear DNA sequences that contain critical mitochondrial promoter sequences as defined by Biswas et al. (T. K. Biswas, J. C. Edwards, M. Rabinowitz, and G. S. Getz, J. Biol. Chem. 262:13690-13696, 1987). The results of these experiments allowed us to extend the definition of essential promoter elements. This extended sequence, -ACTATAAACGatcATAG-, was frequently found in the upstream regulatory regions of nuclear genes. On the basis of these observations, we hypothesized that either (i) a catalytic RNA polymerase related to the mitochondrial enzyme functions in the nucleus of the yeast cell or (ii) a DNA sequence recognition factor is shared by the two genetic compartments. By using cells deficient in the catalytic core of the mitochondrial RNA polymerase (rpo41-) and sensitive assays for transcripts initiating from the nuclear promoter sequences, we have conclusively ruled out a role for the catalytic RNA polymerase in synthesizing transcripts from all of the nuclear sequences analyzed. The possibility that a DNA sequence recognition factor functions in both the nucleus and the mitochondria remains to be tested.